Peran Bidan Dalam Pemberian Suplementasi Tablet Tambah Darah (Ttd) Untuk Pencegahan Anemia Ibu Hamil Di Puskesmas II Kembaran Kabupaten Banyumas - noviyana, alfi (Universitas Harapan Bangsa Purwokerto, 2019)
Supplementary iron tablet coverage does not necessarily reflect the success of the program whenviewed from the current high rate of anemia. The low compliance of pregnant women inconsuming iron supplements is one of the causes of the prevalence of anemia is still high. It occursin the working area of ​​ Health Center II Kembaran. Compliance with pregnant women can befurther improved if the midwife is able to provide nutrition counseling, especially about thebenefits of iron tablets and the health of pregnant women. The purpose of this study is to analyzethe extent of the role of midwives in efforts to prevent anemia. The design of this study usesqualitative methods with a case study approach. Determination of informants is done by PurposiveSampling. Data collection is done by in-depth interviews, field observations and document review.The results of this study Midwives have provided health education to pregnant women abouttablets plus blood (TTD or iron tablet) but have not used the media and have given thesesupplements a minimum of 90 tablets but supervision of the compliance of pregnant women hasnot been maximized. So it needs to involve health cadres, families know the closest people topregnant women improve compliance and utilize KIA book mediakeywords:Anemia, the role of midwives